The Relationship between Psychological Distress, Sociodemographic Variables, and Mental Health for Adolescents During the COVID-19 Pandemic - Tooba Fatima; Ivan Suneel; Abia Nazim; Saima Majeed (Journal of Business and Social Review in Emerging Economies, 2022)
Purpose: The current study examined the impact of demographic correlates such as socio-economic status, family structure, resources, pre-existing physical and mental health conditions, and the home environment on the psychological distress reported by adolescents during a lockdown period.